Optimasi Zoom Meeting Sebagai Media Pembelajaran Virtual Synchronous - I Made Pustikayasa (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
The Covid-19 pandemic indirectly requires educators and participants to master information and communication technology related to the learning process. The use of zoom meetings as a virtual synchronous online learning medium is an option to communicate or face-to-face virtually. Since the Covid-19 pandemic, Zoom has developed various breakthroughs to provide convenience to its users or customers by adding various interesting features. These features can be utilized as much as possible by educators in carrying out online learning so that the learning process can take place well.